Spectrum of vulvar lesions: patient’s anxiety, clinician’s concern and pathologist’s diagnostic challenge - Bhat, Dharitri M.; Mahajan, Vrushali A.; Kumbhalkar, Dinkar T.; Raut, Waman K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: A wide variety of inflammatory, premalignant and malignant lesions can occur on the vulva. Some of the lesions are limited to the vulva, while some also involve other parts of the body. Although vulvar diseases can cause a significant issue in the patients, they are less commonly discussed than those of cervix, uterus and ovary. Most of the asymptomatic lesions remain un-noticed, and are seen during routine gynecological checkups. Common complaints in symptomatic lesions are lumps, discomfort, itching and pain. Since the symptoms are nonspecific; determining the location of the lesion can assist with the diagnosis. Being a genital part with skin covering on outer aspect and mucosal lining inside, it is associated with various dermatological, nutritional, and hormonal as well as sexually transmitted diseases. The present study thus was conducted to categorize vulvar lesions based on their histological diagnosis and also to study the morphological spectrum of precursor lesions for malignancy. Methods: Present study includes all types of vulvar lesions sent for pathological study in the Department of pathology, at GMC Nagpur over the period of one year. Results: Total 34 lesions were studied including a wide diagnostic range from inflammatory, dermatological to benign, premalignant and malignant. Inflammatory lesions including various infections and LSA (Lichen sclerosus atrophicus) were the most commonly seen lesions along with collection of neoplastic lesions. Conclusions: Proper diagnostic categorization of the lesions is essential for initiating therapy and reducing patient’s anxiety. Morphology of these lesions along with their diagnostic significance is discussed.